The Effect of Nonsense Mediated Decay on Transcriptional Activity Within the Novel β-Thalassemia Mutation HBB: c.129delT. (3rd September 2015) - Forster, Luke; Ardakani, Rasha Mesbah; Qadah, Talal; Finlayson, Jill; Ghassemifar, Reza
Abstract: Premature termination codons (PTCs) are caused by mutations in the coding sequences of functional genes resulting in an incorrect assignment of a stop codon. Abnormal and truncated proteins are prevented from being translated due to the rapid degradation of mRNA carrying these mutations by an RNA surveillance mechanism referred to as nonsense mediated decay (NMD). Recently, a novel mutation in a patient from Thailand with the clinical diagnosis of Hb E ( HBB : c.79G > A)/β 0 -thalassemia (Hb E/β 0 -thal) and whose molecular analysis demonstrated a novel mutation in the β-globin gene, HBB : c.129delT, was reported. The result of this deletion is a frameshift (FSC) resulting in a PTC at codon 60. We have analyzed the impact of this mutation on transcription and translation of the affected β-globin gene using an in vitro model. The quantitative real-time polymerase chain reaction (qReTi-PCR) analysis revealed that this nucleotide mutation resulted in marked mRNA degradation, which we attributed to the NMD mechanism and as such, the expected deleterious truncated HBB was not generated. This result highlights a valuable application of our in vitro gene expression model that can be used to predict possible molecular pathology for any given nucleotide mutations.